Glucocerebrosidase: reconstitution from macromolecular components depends on acidic phospholipids (Short Communication) - Ho, Mae Wan (1973)
The reconstitution of glucocerebrosidase activity from its inactive macromolecular components depended on acidic membrane phospholipids.